Hypergastrinaemia in Chronic Renal Failure. Issue 5794 (22nd January 1972) - Korman, M. G.; Laver, M. C.; Hansky, J.
Abstract : Fasting serum gastrin was measured by radioimmunoassay in 89 patients with chronic renal failure. When the serum creatinine level was used as an index of the degree of renal impairment serum gastrin rose proportionately with the degree of renal failure. Haemodialysis did not significantly alter serum gastrin levels but renal transplantation tended to return them towards normal. This study indicates that the kidney has a role in the degradation of gastrin.